Incidence of acute cholecystitis underwent cholecystectomy in incident dialysis patients: a nationwide population-based cohort study in Korea - Hanlim Choi; Soon Kil Kwon; Joung-Ho Han; Jun Su Lee; Gilwon Kang; Minseok Kang (The Korean Society of Nephrology, 2022)
Background Patients on dialysis have numerous gastrointestinal problems related to uremia, which may represent concealed cholecystitis. We investigated the incidence and risk of acute cholecystitis in dialysis patients and used national health insurance data to identify acute cholecystitis in Korea. Methods The Korean National Health Insurance Database was used, with excerpted data from the insurance claim of the International Classification of Diseases code of dialysis and acute cholecystitis treated with cholecystectomy. We included all patients who commenced dialysis between 2004 and 2013 and selected the same number of controls via propensity score matching. Results A total of 59,999 dialysis and control patients were analyzed; of these, 3,940 dialysis patients (6.6%) and 647 controls (1.1%) developed acute cholecystitis. The overall incidence of acute cholecystitis was 8.04-fold higher in dialysis patients than in controls (95% confidence interval, 7.40-8.76). The acute cholecystitis incidence rate (incidence rate ratio, 23.13) was especially high in the oldest group of dialysis patients (aged ≥80 years) compared with that of controls. Dialysis was a significant risk factor for acute cholecystitis (adjusted hazard ratio, 8.94; 95% confidence interval, 8.19-9.76). Acute cholecystitis developed in 3,558 of 54,103 hemodialysis patients (6.6%) and in 382 of 5,896 patients (6.5%) undergoing peritoneal dialysis. Conclusions Patients undergoing dialysis had a higher incidence and risk of acute cholecystitis than the general population. The possibility of a gallbladder disorder developing in patients with gastrointestinal problems should be considered in the dialysis clinic.